Strategic Information and Communication Technology Skills and Effectiveness of Library Services in Jordan - Al-Refai, Abdalla Nayef Saleh (2011)
The purpose of this study is to examine the information and communication technology skills and effectiveness of library services in Jordan. Presently, Information and Communication Technology is important in this era and librarians must use this technology to provide better services in libraries. This study was undertaken among librarians in Yarmouk university. Yarmouk university library has the largest number of librarians in Jordan. This study focuses on information and communication technology skills and effectiveness of library services. In the study 60 librarians from Yarmouk university library gave their responses. Based on the data provided by the librarians descriptive and correlation analyses were carried out. The results of the study suggest that information communication technology skills namely literacy, skills, and attitude are related to effectiveness of library services.